Genetically Engineered Thompson Seedless Grapevine Plants Designed for Fungal Tolerance: Selection and Characterization of the Best Performing Individuals in a Field Trial - Ortega-Tapia, L (Kluwer Academic Publishers, 2015)
The fungi Botrytis cinerea and Erysiphe necator are responsible for gray mold and powdery mildew diseases, respectively, which are among the most devastating diseases of grapes. Two endochitinase (ech42 and ech33) genes and one N-acetyl-β-d-hexosaminidase (nag70) gene from biocontrol agents related to Trichoderma spp. were used to develop a set of 103 genetically modified (GM) ‘Thompson Seedless’ lines (568 plants) that were established in open field in 2004 and evaluated for fungal tolerance starting in 2006. Statistical analyses were carried out considering transgene, explant origin, and plant response to both fungi in the field and in detached leaf assays. The results allowed for the selection of the 19 consistently most tolerant lines through two consecutive years (2007–2008 and 2008–2009 seasons). Plants from these lines were grafted onto the rootstock Harmony and established in the field in 2009 for further characterization. Transgene status was shown in most of these lines by Southern blot, real-time PCR, ELISA, and immunostrips; the most tolerant candidates expressed the ech42–nag70 double gene construct and the ech33 gene from a local Hypocrea virens isolate. B. cinerea growth assays in Petri dishes supplemented with berry juices extracted from the most tolerant individuals of the selected population was inhibited. These results demonstrate that improved fungal tolerance can be attributed to transgene expression and support the iterative molecular and physiological phenotyping in order to define selected individuals from a population of GM grapevines. © 2014, Springer International Publishing Switzerland.
Keywords: Botrytis tolerance; Transgenic grapevine; Field trial; Chitinase; Thompson Seedless